Gene polymorphisms of cellular senescence marker p21 and disease progression in non-alcohol-related fatty liver disease - Aravinthan, Aloysious (Landes Bioscience, 2014)
Non-alcohol-related fatty liver disease (NAFLD) encompasses a wide spectrum, ranging from steatosis alone to steatohepatitis and fibrosis. Presence of steatohepatitis and fibrosis are key hallmarks of disease progression. Previous studies have demonstrated an association between hepatocyte p21 expression and fibrosis stage in NAFLD. The aim of this study is to investigate the association between the variants of CDKN1A, which encodes p21, and disease progression in NAFLD. To this end, the relation between CDKN1A polymorphism and liver fibrosis was studied in 2 cohorts of biopsy-proven NAFLD patients from UK (n = 323) and Finland (n = 123). Genotyping was performed using DNA isolated from lymphocytes collected at the time of liver biopsy. The findings of the UK cohort were tested in the Finnish cohort. Both the UK and Finnish cohorts were significantly different from each other in basic demographics. In the UK cohort, rs762623, of the 6 SNPs across CDKN1A tested, was significantly associated with disease progression in NAFLD. This association was confirmed in the Finnish cohort. Despite the influence on fibrosis development, SNPs across CDKN1A did not affect the progression of liver fibrosis. In conclusion, CDKN1A variant rs762623 is associated with the development but not the propagation of progressive liver disease in NAFLD.